Infant Preference for Natural Texture Statistics is Modulated by Contrast Polarity. (31st March 2014) - Balas, Benjamin; Woods, Rebecca
<x xml:space="preserve">Abstract</x> Adult observers are sensitive to statistical regularities present in natural images. Developmentally, research has shown that children do not show sensitivity to these natural regularities until approximately 8–10 years of age. This finding is surprising given that even infants gradually encode a range of high‐level statistical regularities of their visual environment in the first year of life, We suggest that infants may in fact exhibit sensitivity to natural image statistics under circumstances where images of complex, natural textures, such as a photograph of rocks, are used as experimental stimuli and natural appearance is substantially manipulated. We tested this hypothesis by examining how infants' visual preference for real versus computer‐generated synthetic textures was modulated by contrast negation, which produces an image similar to a photographic negative. We observed that older infants' (9‐months of age) preferential looking behavior in this task was affected by contrast polarity, suggesting that the infant visual system is sensitive to deviations from natural texture appearance, including (1) discrepancies in appearance that differentiate natural and synthetic textures from one another and (2) the disruption of contrast polarity following negation. We discuss our results in the context of adult texture processing and the "perceptual narrowing" of visual recognition during the first year of life.